EXPERIENCE REPORT OF PREGNANCY DURING PEDIATRIC RESIDENCY - Negreiros, Bianca Lopes de Miranda (Cadernos ESP, 2024)
The increase in the enrollment of female physicians in residency programs has led to a growing rate of residents experiencing pregnancy during their specialization years, but the association between pregnancy and residency remains a dilemma in the medical field. To describe the experiential account of two pregnancies lived by a physician during her pediatric residency. This is an experiential report conducted by a pediatric resident in Fortaleza, from May 2022 to January 2024, with data collected under the author's observation and analyzed through reflection. Several challenges are faced by women when experiencing pregnancy during the residency phase, requiring greater effort to find ways to overcome them. Personal effort and cooperation from residency program coordinations are crucial for a healthy confrontation of this reality.
Keywords: Pregnancy; Medical Residency; Pediatrics